Refracture after locking compression plate removal in displaced midshaft clavicle fractures after bony union: a retrospective study - Ho-Youn Park; Seok-Jung Kim; Yoo-Joon Sur; Jae-Woong Jung; Chae-Gwan Kong (Clinics in Shoulder and Elbow, 2021)
Background A midshaft clavicle fracture is a common fracture that typically responds well to open reduction and internal fixation (ORIF). However, refracture can occur after implant removal (IR). This study aimed to analyze the rate of refracture and related factors after removal of the locking compression plate (LCP) for displaced midshaft clavicle fractures. Methods We retrospectively reviewed the medical records of 201 patients who had undergone ORIF with LCP for midshaft clavicle fractures after IR after bony union from January 2011 to May 2018 at our institute. We evaluated basic demographic characteristics and radiographic parameters. All patients were treated with an LCP for primary fracture. The patients were divided into two groups: a refracture group that experienced a second fracture within 1 year after IR and a no-fracture group. Results There were four cases (1.99%) of refracture; three were treated conservatively, while one was treated surgically. All patients achieved bony union. The average interval between refracture and IR was 64 days (range, 6–210 days). There was a significant difference in classification of fractures (AO Foundation/Orthopaedic Trauma Association [AO/OTA] classification) between the two groups. However, other patient demographics and radiographic measurements between refracture and IR, such as bone diameter, showed no significant difference between the two groups. Conclusions This study showed that one in 50 patients suffered from refracture after removal of the LCP. Thus, if patients desire IR, the surgeon should explain that there is a relatively higher possibility of refracture for cases with simple or segmental fractures than for other types of fracture.